Akad Musyarakah Dari Teori Ke Praktik (Studi Kasus di Bank Syariah Mandiri KCP Majenang) - Imron Hamzah (Fakultas Syariah UIN Prof. K.H. Saifuddin Zuhri, 2023)
One of the solutions to avoid usury practices in banking is the implementation of the musyarakah contract. Among the banks that have applied the musyarakah contract is Bank Syariah Mandiri at its branch office in Majenang, located at Jalan Diponegoro No. 60, Majenang. However, in practice, it may not be possible to implement it 100% in accordance with the fiqh concept formulated by past scholars. There are several transformations of the fiqh concept, including in the form of musyarik, contract motifs, collateral requirements, types of business, profit-sharing distribution, profit-sharing ratios, the presence of penalties, musyarik's concern for the business being conducted, and the allocation of work. Some of these transformations have been legalized by the Fatwa of the National Sharia Board (DSN-MUI), such as collateral requirements, while others contradict the Fatwa of the DSN-MUI, such as in the event of losses in the business conducted. Additionally, some aspects align with the opinion of a contemporary scholar, particularly regarding the division of labor.